The Role Of Time In Place Attachment Case Study: Javaherdeh Recreation Area Of Ramsar - Nejati, Seyedeh Haniyeh; Mahdavi, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
Quantitative studies have shown that the duration of the relationship is considered an important variable in the development of place attachment. However, the study of place attachment and the meaning of this attachment do not provide us much information. The present study was conducted to explain the relationship between time and place attachment in two groups including travelers and natives who were presented in Javaherdeh region of Ramsar. The results showed that the duration of the relationship plays an important role in the process that connects people with place and finally, there are different ways in which the time is effective in the formation of meanings in a place.
Keywords: place attachment; time; Javaherdeh region of Ramsar